Azetidine synthesis enabled by photo-induced copper catalysis via [3+1] radical cascade cyclization - Jianye Li; Lu Yu; Yun Peng; Bin Chen; Rui Guo; Xiaodong Ma; Xiao-Song Xue; Yunkui Liu; Guozhu Zhang (The Innovation, 2022)
Azetidines are an important type of saturated, highly strained, four-membered, nitrogen-containing heterocyclic compound. These compounds serve as important raw materials, intermediates, and catalysts in organic synthesis, as well as important active units in amino acids, alkaloids, and pharmaceutically active compounds. Thus, the development of an efficient and concise method to construct azetidines is of great significance in multiple disciplines. In this work, we reported on the photo-induced copper-catalyzed radical annulation of aliphatic amines with alkynes to produce azetidines. This reaction occurred in a two- or three-component manner. The alkynes efficiently captured photogenerated α-aminoalkyl radicals, forming vinyl radicals, which initiated tandem 1,5-hydrogen atom transfer and 4-exo-trig cyclization. Density functional theory calculations indicated that the tertiary radical intermediate was critical for the success of cyclization. In addition, the resulting saturated azetidine scaffolds possessed vicinal tertiary-quaternary and even quaternary-quaternary centers.